Ways of Professional and Innovative Integration in the Field of Professional Art Education in China - Wang, Jing (Современное образование, 2025)
This article notes that, due to the modernization of the education system in modern China, approaches to the training of artistic personnel are changing. An assessment is given of how the process of integrating international experience is reflected in the course of training, which, in synthesis with national traditions, turns into innovations. The article describes the options for organizing the educational process in Chinese colleges (the Shenzhen School of Art) and universities (the School of Architecture and Environmental Art at the Institute of Fine Arts in Sichuan Province), which create innovative models for the formation of necessary competencies for future specialists, taking into account the advanced achievements of world pedagogy, art, and their own experience. The theoretical basis of the research consists of works that study the phenomenon of integration in education. The author studied: methodological principles of art education, the model of multi-level artist training systems, and regulatory and methodological frameworks for the educational process. Scientific and theoretical methods included the analysis of the problem, the study of literature on the topic, program documents, and exhibition material. The object of the research is higher and secondary art education in China at the beginning of the 21st century. The subject of the research is the theoretical understanding and practical application of “integration” as a methodological principle for building multi-level artist training in Chinese universities and colleges based on the idea of synthesizing continuity, traditions, modern trends, and innovations. The purpose of the study is to identify options for applying the concept of “professional and innovative integration” in the artistic and creative training of future specialists in the system of secondary and higher professional art education in modern China. The tasks set included the study of various aspects of the concept of “professional and innovative integration” through the prism of artistic and creative training, a description of the approaches to integration, and their interpretation that have developed in various educational institutions of China at different levels.